Data repository for "Increase in insurance losses caused by North Atlantic hurricanes in a warmer climate" ... - Comola, Francesco (Mendeley Data, 2024)
This data is associated with the article "Increase in insurance losses caused by North Atlantic hurricanes in a warmer climate". The dataset contains the input files and the scripts to reproduce the results presented in the paper. - "IndexationFactors.csv" contains insured loss indexation factors based on the yearly values of US Gross Domestic Product (GDP) deflator (The World Bank, 2023) and US property insurance gross premium (Organisation for Economic Co-operation and Development, 2023). - "HURDAT2_processed.csv" contains information on hurricane physical properties extracted from the HURDAT2 hurricane dataset, including name, date of occurrence, landfall speed, and maximum lifetime category - "PCS_processed.csv" contains information on wind-driven hurricane losses extracted from Verisk's Property Claim Services datasets, including the original and the indexed property insurance losses caused by hurricanes since 1950. - "NFIP_processed.csv" contains information on flood-driven hurricane losses extracted ...